Long-Term Survival, Stroke Recurrence, and Life Expectancy After an Acute Stroke in Australia and New Zealand From 2008–2017: A Population-Wide Cohort Study. Issue 8 (14th April 2022) - Peng, Yang; Ngo, Linh; Hay, Karen; Alghamry, Alaa; Colebourne, Kathryn; Ranasinghe, Isuru
Abstract : Background: Data on long-term outcomes following an acute stroke are sparse. We assessed survival, risk of recurrent stroke and loss in life expectancy following an acute stroke using population-wide data from Australia and New Zealand. Methods: We included all adults with the first stroke hospitalization during 2008 and 2017 at all public and most private hospitals. Patients were followed up to 10 years after the stroke by linkage to each region's Registry of Deaths and subsequent hospitalizations. Flexible parametric survival modeling was used to estimate all-cause mortality, stroke recurrence, and loss in life expectancy. Competing risk model was used when estimating the risk of stroke recurrence. Results: Three hundred thirteen thousand one hundred sixty-two patients were included (mean age 73.0±14.6 y, 52.0% males) with ischemic stroke (175 547, 56.1%) being the most common, followed by hemorrhagic stroke (77 940, 24.9%) and unspecified stroke (59 675, 19.1%). The overall survival probability was 79.4% at 3 months, 73.0% at 1 year, 52.8% at 5 years, and 36.4% at 10 years. Cumulative incidence of stroke recurrence was 7.8% at 3 months, 11.0% at 1 year, 19.8% at 5 years, and 26.8% at 10 years. Hemorrhagic stroke was associated with greater mortality (hazard ratio, 2.02 [95% CI, 1.99–2.04]) and recurrent stroke (hazard ratio, 1.63 [95% CI, 1.59–1.67]) compared with ischemic stroke. Female sex (hazard ratio, 1.10 [95% CI, 1.09–1.11]) and increasing age (≥85 years versus 18–54 years: hazard ratio, 7.36 [95% CI, 7.15–7.57]) were also associated with increased mortality. Several risk factors including atherosclerotic coronary and noncoronary vascular disease, cardiac arrhythmia, and diabetes were associated with increased risk of mortality and recurrent stroke. Compared with the general population, an acute stroke was associated with a loss of 5.5 years of life expectancy, or 32.7% of the predicted life expectancy, and was pronounced in patients with a hemorrhagic stroke (7.4 years and 38.5% of predicted life expectancy lost). Conclusions: In this population-wide study, death and recurrence of stroke were common after an acute stroke and an acute stroke was associated with considerable loss in life expectancy. Further improvements in treatment and secondary prevention of stroke are needed to reduce these risks.